Studies on the Enantiomers of RC-33 as Neuroprotective Agents: Isolation, Configurational Assignment, and Preliminary Biological Profile. Issue 11 (7th September 2013) - Rossi, Daniela; Pedrali, Alice; Marra, Annamaria; Pignataro, Luca; Schepmann, Dirk; Wünsch, Bernhard; Ye, Lian; Leuner, Kristina; Peviani, Marco; Curti, Daniela; Azzolina, Ornella; Collina, Simona
ABSTRACT In this study we addressed the role of chirality in the biological activity of RC-33, recently studied by us in its racemic form. An asymmetric synthesis procedure was the first experiment, leading to the desired enantioenriched RC-33 but with an enantiomeric excess (ee) not good enough for supporting the in vitro investigation. An enantioselective high‐performance liquid chromatography (HPLC) procedure was then successfully carried out, yielding both RC-33 enantiomers in amounts and optical purity suitable for the pharmacological study. The absolute configuration of pure enantiomers was easily assigned exploiting the asymmetric synthesis previously devised. As emerged in the preliminary in vitro biological investigation, (S)‐ and (R)-RC-33 possess a comparable affinity towards the σ1 receptor and a very a similar behavior in the calcium influx assay, resulting in an equally effective σ1 receptor agonist. Overall, the results obtained so far suggest that the interaction with the biological target is nonstereoselective and leads us to hypothesize that there is a lack of stereoselectivity in the biological activity of RC-33. Chirality 25:814–822, 2013. © 2013 Wiley Periodicals, Inc.